Kekuatan Alat Bukti Sertifikat Elektronik Hak Atas Tanah Pada Perkara Perdata Di Pengadilan - Tsamirah Zarifah Ratmin; Adonia Ivonne Laturette; Pieter Radjawane (Faculty of Law Universitas Pattimura, 2023)
Technological developments can be seen by the emergence of new electronic-based evidence, one of which is electronic documents. Law Number 11 of 2008 concerning Electronic Information and Transactions states that electronic documents are valid evidence as long as what is contained in them can be accessed, displayed, guaranteed integrity and can be accounted for. The method used in this study is Normative Juridical (legal research). And using an approach by reviewing legislation, the type of legal research used by reviewing literature and secondary data. The source of legal material used consists of primary, and secondary which are analyzed qualitatively. The results of this study show that electronic certificates can be used as valid evidence in civil cases in court as stipulated in the ITE Law as long as the provisions of the regulations, and produce electronic documents in which there are electronic signatures and the document can be accessed, displayed, guaranteed its integrity and can be accounted for, in addition to electronic documents in the form of electronic certificates This is also an expansion of evidence in civil procedural law.